How to facilitate employees’ green behavior? The joint role of green human resource management practice and green transformational leadership - Chen, Tingting; Wu, Zhanyong (Frontiers in Psychology, 2022)
Given the severity of today's environmental issues, companies are increasingly making green concepts a key component of their operational strategies. As an essential complement to corporate environmental strategy, employees' green behavior has received attention from all sectors of society. Based on resource conservation theory, this study explores the formation mechanism of employees' green behaviors in enterprises starting from two green management tools: green human resource management (HRM) practices and green transformational leadership. Through two-stage questionnaire research, 296 sample data points were obtained, and the research hypotheses were tested by using linear regression analysis. The results showed that green HRM practices in enterprises enhance employees' green mindfulness and thus stimulate their green behaviors and that green transformational leadership and green self-efficacy play a positive moderating role in the above relationship. These results support the applicability of resource conservation theory in green management and suggest that green HRM practices and green transformational leadership can be used together in the process of green management.